Utilización de la cerdaza en la alimentación de ganado de carne. Una alternativa para evitar la contaminación ambiental - Campabadal Herrero, Carlos (Universidad de Costa Rica, 2013)
Enviromental and economic impact of the use of swine waste on beef catle feeding program. Swine waste can be used as feed for beef cattle on feedlot. Manual and mechanical methods are the two ways to collect this product. The processing method and the composition of the pig diet affect the composition of the swine manure. Calcium level of swine waste is the most problematic nutrient. Swine waste production varies from 0.24 Ton/year for starter pigs to 2.4Ton for lactating sows and her litter. It is necessary the fecal production of 20 pigs to fed a steer. There are four processing methods which include dry, silage, chemical preservation and liquid: solid separation. It is non recomendable to use in swine diets, except at 10% level in gestating sows. Feeding beef cattle, the maximum level of swine waste is 60% plus other agricultural byproducts. Feed consumption varies f rom 1 0 to 1 2 Kg of fresh product and dairy gains from 500 to 900 g /day, depending on the genetic potencial of the animal.